The corrosion of solid solution Mg-Sn binary alloys in NaCl solutions. (20th February 2019) - Cain, T.W.; Glover, C.F.; Scully, J.R.
Abstract: The corrosion behavior of solid solution Mg-xSn (x = 1, 5, 10 wt%) alloys is explored as a function of Sn content in chloride-containing conditions. A suite of in situ electrochemical techniques and an in situ scanning vibrating electrode technique (SVET) is utilized to assess free corrosion rates and the extent of cathodic activation. The latest advances in improving the corrosion resistance of Mg alloys have demonstrated that micro-alloying with As or Ge can greatly lower corrosion rates compared to pure Mg and retard cathodic activation to a substantial degree. To broaden the options for suitable non-toxic alloying elements beyond Ge, the current article demonstrates a decreasing corrosion rate by 77%, 85% and 95% for Sn additions of 1%, 5% and 10% (wt%) respectively, when compared to HP Mg freely corroding in 0.6 M aqueous NaCl. A corrosion film formed on Mg-10Sn which displays superior barrier properties. Polarization resistance (Rp ) values consistently one order of magnitude greater than that obtained on HP Mg, and the other Mg-Sn alloys, over a 24 h immersion period is demonstrated. Furthermore, the extent of cathodic activation for Mg-10Sn is shown to be reduced by 94% relative to HP Mg. The work presented herein provides advancements in the understanding of corrosion resistant Mg alloys and is pertinent to the potential use of Mg-Sn alloys in transport applications, battery electrode materials and as a candidate sacrificial anode for the cathodic protection of Mg alloy AZ31B-H24. Prospects for protection are discussed.